(untitled) (New York, 1990)
Contents: Genberal Principles, Drugs Acting at Synaptic and Neuroeffector Junctional Sites, Drugs Acting on the Central Nervous System, Autacoids: Drugs Theraphy of Inflammation, Water, Salts, and Ions, Drugs Affecting enal Function and Electrolyte Metabolism....
Keywords: Dược học,Pharmacology